Determining the Geographic Location of Internet Hosts - Lakshminarayanan, Subramanian; Padmanabhan, Venkat (2000)
Knowing the physical location of users is a prerequisite for location-aware computing. Much work has gone into the user location problem in the context of wireless networks and mobile hosts. We present and evaluate three distinct techniques - GeoTrack, GeoPing , and GeoCluster for determining the geographic location of Internet hosts. GeoTrack infers location based on the DNS names of the host of interest or other neaby network nodes. GeoPing uses network delay measurements from geographically distributed locations to triangulate the coordinates of the host. GeoCluster couples partial host-to-location mapping information obtained (indirectly) from Web sites with BGP routing information to infer location of the host of interest. Using extensive and varied data sets, we evaluate the performance of these techniques. We also discuss the strengths and weaknesses of each technique.